Secondary analysis of a university‐based weight loss program in on‐campus versus off‐campus employees. (4th June 2022) - Clina, Julianne G.; Pan, Zhaoxing; Wyatt, Holly R.; Peters, John C.; Hill, James O.; Sayer, R. Drew
Abstract: Introduction: Many barriers prevent individuals from regularly engaging in physical activity (PA), including lack of time and access to facilities. Providing free gym membership close to one's work may alleviate both time and financial barriers, increase PA, and result in greater weight loss. The purpose of this secondary analysis was to determine if gym usage, self‐reported leisure PA, and weight loss differed between participants working on the University of Colorado Anschutz Medical Campus (ON) versus working off‐campus (OFF) during a 6‐month weight loss trial. Methods: 117 adults (ON, n  = 62; OFF, n  = 55) with overweight or obesity received free gym memberships for the duration of trial. Average gym check ins/week, self‐report leisure PA, weight, and fat and lean mass were compared between groups. Results: ON reported more check‐ins than OFF (ON, 0.93 ± 0.16 times/week; OFF, 0.55 ± 0.10 times/week p  = 0.038). Both groups reported increased leisure PA, with ON reporting more leisure PA than OFF at month 4. Both groups had reductions in weight and fat mass, which were similar between groups. Conclusion: Gym usage in both groups was low, suggesting that convenient and free gym access only marginally promoted use of provided facilities, likely having little additional impact on PA and weight change. CLINICAL TRIAL REGISTRATION: The parent trial was registered at clinicaltrials.gov : NCT02627105.